2022
DOI: 10.1038/s41598-022-12830-0
|View full text |Cite
|
Sign up to set email alerts
|

Evolutionary game analysis of opportunistic behavior of Sponge City PPP projects: a perceived value perspective

Abstract: Sponge City Public Private Partnership (PPP) project is a significant step to promote the construction of resilient city and sustainable development. Private companies take advantage of information asymmetry and regulatory loopholes to take opportunistic behavior, which affects the project delivery quality and public interests. In order to reveal the decision-making mechanism of the main stakeholders, this paper constructs an evolutionary game model of private companies, citizens and the government from a fres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 46 publications
1
12
0
Order By: Relevance
“…The effect of family income on WTP for urban green infrastructure varied from city to city. Some found that respondents' income had a statistically positive effect on WTP [44,[51][52][53]; this is in line with our study in Nanning, Chongqing and Xi'xian New City. However, in the case cities of Pingxiang, Zhenjiang, and Qingdao, the family income was not significantly related to WTP, for urban green infrastructure which is in line with the results of [46].…”
Section: Results Of Binary Logistic Regressionsupporting
confidence: 91%
“…The effect of family income on WTP for urban green infrastructure varied from city to city. Some found that respondents' income had a statistically positive effect on WTP [44,[51][52][53]; this is in line with our study in Nanning, Chongqing and Xi'xian New City. However, in the case cities of Pingxiang, Zhenjiang, and Qingdao, the family income was not significantly related to WTP, for urban green infrastructure which is in line with the results of [46].…”
Section: Results Of Binary Logistic Regressionsupporting
confidence: 91%
“…Due to bounded rationality, companies may not always make optimal choices and need to adjust and improve their strategies through continuous information interaction and learning (Güth, 2021;Zhao et al, 2022). Evolutionary game theory provides a framework for modeling companies' suboptimal decisions and adjustments in their strategies.…”
Section: Discussionmentioning
confidence: 99%
“…It means both the public and private sectors will take active behaviors when the valence perceptions of their active behaviors are more significant than their negative behaviors, and the cost perceptions of their active behaviors are lower than that of their negative behaviors. However, in reality, some factors prevent the system from reaching the optimal state, such as high-cost perception of active behavior by game players, game players’ bounded rationality making their decisions subjective or overconfident, and game players’ different risk attitudes and reference points, et al ( Wu et al, 2020 ; Zhao et al, 2022 ).…”
Section: Model Solutionmentioning
confidence: 99%